City of Liverpool : Maternity and Child Welfare
1928-01 1928 1920s 5 pages Maternity and Child Welfare. Work at Ante-Natal Centres during January 1928, as per Returns received. P.2883.250.10/27.Est CONSULTATIONS. HOME VISITS. References to Public Health Department No. of Sessions held during the month. New Cases. Total Attendances. Attendances at Classes. New Cases. Total Visits. Carnegie Centre 5 45 152 99 9 70, Everton Road 8 90 322 148 24 15-17, Upper Parliament Street 8 88 308 27 334, Netherfield Road 8 84 311 St. Martin's Hall, Scotland Road 9 69 367 49 Parish Hall, Walton 4 45 153 20 9 201, Rathbone Road 5 19 110 47 196, Beaufort Street 4 16 69 Norwood Grove 4 28 120 Garston Technical School 4 9 53 Liverpool Maternity Hospital 26 581 1658 Child Welfare Association No returns. Liverpool Babies' Hospital, Wootton 4 3 23 Royal Infirmary. 9 41 204 12 98 1138 3870 363 81 292/824/1/124-125